Influence of synthesis on composite/laminated starch-gelatine based biopolymer film properties - Šuput, Danijela; Popović, Senka; Ugarković, Jovana; Hromiš, Nevena (Analecta Technica Szegedinensia, 2022)
Biopolymer films have an increasing share in the packaging material sector due to a number of advantages: availability, cheapness, easy processing, degradability, etc. On the other hand, numerous methods have been developed to optimize their unfavorable properties (weaker mechanical characteristics, hydrophilicity, etc.). This paper examines the influence of the synthesis method on starch-gelatin films properties. The starch-gelatin film was synthesized in a ratio 1:1 as a composite film (C). The second sample was obtained by gelatin film lamination on starch film (L). Plain starch film was used as a control (0). Mechanical, structural and physico-chemical properties of importance for the application of packaging materials were tested on the obtained samples. All the obtained biopolymer films were transparent and easy to handle. FTIR spectroscopy identified all characteristic groups and bonds formed in composite and laminated films. The results showed a significant contribution of gelatin in the developed biopolymer films compared to the control sample. Gelatin incorporated as a film component or as a separate layer improved mechanical properties and water solubility. Slight differences were observed between composite and laminated films because the effect of the method of added gelatin is minimal compared to the sample without the addition of gelatin.